2022
DOI: 10.2196/35882
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Use of Chatbots in Public Health: Scoping Review

Abstract: Background Chatbots are computer programs that present a conversation-like interface through which people can access information and services. The COVID-19 pandemic has driven a substantial increase in the use of chatbots to support and complement traditional health care systems. However, despite the uptake in their use, evidence to support the development and deployment of chatbots in public health remains limited. Recent reviews have focused on the use of chatbots during the COVID-19 pandemic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 58 publications
1
62
0
Order By: Relevance
“…However, chatbots are relatively new to the public health arena. A 2022 scoping review assessing the research base for the use of chatbots in public health identified the need for more research describing the development process and evaluating the efficacy and effectiveness of these chatbots [ 25 ]. The breadth of information shared in both this paper and an upcoming paper evaluating the feasibility and acceptability of the PrEPBot will begin to address this gap in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…However, chatbots are relatively new to the public health arena. A 2022 scoping review assessing the research base for the use of chatbots in public health identified the need for more research describing the development process and evaluating the efficacy and effectiveness of these chatbots [ 25 ]. The breadth of information shared in both this paper and an upcoming paper evaluating the feasibility and acceptability of the PrEPBot will begin to address this gap in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…14 However, their usability can be perceived as limited by the algorithms driving them, their scalability, or the lack of privacy perceived by their users. [13][14][15][16][17] To our knowledge, there is no chatbot currently that specifically meets the needs of PWH. We could not find a chatbot using any local languages of African countries in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated the rising development of chatbots in chronic diseases, e.g., for therapeutic education in diabetes 16 or sickle‐cell disease management 14 . However, their usability can be perceived as limited by the algorithms driving them, their scalability, or the lack of privacy perceived by their users 13–17 …”
Section: Introductionmentioning
confidence: 99%
“…Previous research into the efficiencies and effectiveness of conversational AI solutions in healthcare is limited [Wilson et al, 2022]. The majority of studies investigating chatbots in a healthcare setting often only rely on brief follow-up periods [Vaidyam et al, 2019], trials in non-clinical settings [Fitzpatrick et al, 2017], or use differing definitions of “recovery” [Meadows et al, 2020].…”
Section: Introductionmentioning
confidence: 99%